2018
DOI: 10.1253/circj.cj-17-1310
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Neurological Severity and Outcomes of Ischemic Stroke ― 5-Year Single-Center Observational Study ―

Abstract: Overall ischemic stroke showed a fairly even distribution among the 4 seasons. Cardioembolic stroke was more common in winter. Ischemic stroke patients had more moderate-to-severe initial neurological deficits in winter and spring. Poor clinical outcomes at 1 year were generally similar among the seasons. Ischemic stroke is not necessarily a winter-dominant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
16
2
Order By: Relevance
“…Some studies have reported that ischemic stroke occurrence was significantly higher during spring and autumn than in summer [4,5]. However, another study stated that there was a fairly even distribution of ischemic stroke over all 4 seasons [6] and a recent meta-analysis showed very little seasonal variation [7]. Also, our analysis of variance of the monthly number of ischemic stroke between 2015 and 2019 was not significant.…”
Section: What Could We Hypothesize For This Observation?contrasting
confidence: 72%
“…Some studies have reported that ischemic stroke occurrence was significantly higher during spring and autumn than in summer [4,5]. However, another study stated that there was a fairly even distribution of ischemic stroke over all 4 seasons [6] and a recent meta-analysis showed very little seasonal variation [7]. Also, our analysis of variance of the monthly number of ischemic stroke between 2015 and 2019 was not significant.…”
Section: What Could We Hypothesize For This Observation?contrasting
confidence: 72%
“…Some studies report that ischaemic stroke events are significantly higher during spring and autumn than in summer 17,18 and, in our case, the drop in stroke admissions has occurred during the beginning of spring. However, another study stated that there was a fairly even distribution of ischaemic stroke over all four seasons 19 and a recent meta-analysis showed very little seasonal variation 20 .…”
Section: Accepted Articlementioning
confidence: 99%
“…Since the first reported case in early December 2019, severe acute respiratory coronavirus 2 (SARS-CoV-2) infection, known as Coronavirus Disease 2019 (COVID- 19), has become pandemic so rapidly that healthcare systems are overwhelmed [5][6][7] . In Spain, by April 19th,195,944 cases and 20,453 deaths have been confirmed 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, among those patients, 135 patients (acute ischemic stroke, n = 118; TIA, n = 17) who underwent MPRAGE for the evaluation of the aortic arch and carotid plaques were included in this retrospective observational study. Patient characteristics including past medical history and stroke risk factors were collected using a database in our stroke center (the National Cerebral and Cardiovascular Center stroke registry; Clinical Trial.gov: NCT02251665) [32,33].…”
Section: Study Populationmentioning
confidence: 99%